(untitled) (Journal of actual problems of jurisprudence, 2019)
The article deals with the present status of the Caspian sea. The author analyses in detail the basic issues and multilateral intergovernmental agreements that regulate the activities on the sea and the adjacent areas. The classification of major principles is offered for the readers. Possible future perspectives of development in this area are offered for the readers. Applicable regional aspects of the Law of the sea are mentioned in the work. The article touches on the issues of the Caspian sea status. Some argreements in that field are considered in more detail. The positions of littoral countries is scrutinized as well.